Negative Feedback Loop between Banks and Sovereigns in the Euro Area – Experience of the Crisis and Post-Crisis Perspective - Stawasz-Grabowska, Ewa (Comparative Economic Research. Central and Eastern Europe, 2020)
The euro area crisis was characterised by a negative feedback loop between banks and sovereigns. The paper aims to indicate the genesis of this phenomenon and to determine the scale of its operation during the crisis and post-crisis conditions, as well as to identify the threats it brings. In addition, the paper discusses the actions that have been taken so far at the euro area level to reduce the feedback loop and the existing challenges in this area. The following hypothesis has been formulated: in the post-crisis conditions the euro area remains vulnerable to the sovereign-bank nexus, which in particular stems from the very legacy of the crisis, bank-based financial system, as well as incomplete reforms of the euro area institutional architecture. The research methods include data selection and evaluation as well as descriptive statistics. The main contribution of the study stems from the adoption of a post-crisis perspective and the assessment of the loop with the use of the most recent data and in relation to the crisis period. The results show that in the post-crisis period, a reduction in interconnectedness has been observed, although it has not been evenly experienced by all euro area countries. At the same time, despite some progress in recent years, institutional reforms aimed at breaking the sovereign-bank nexus are far from complete.